ANALISIS MAKNA MAJAS METONIMI PADA LIRIK LAGU JEPANG - Elviani Saragih; Hermandra Hermandra; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The study described the meaning of metonymy of Japanese song lyrics. The purpose of this study is to describe the meaning, analyze and describe the relationship metonymy in Japanese song lyrics. This study uses descriptive method. The data is taken from Japanese lyrics by Spyair. The results show that metonymy in Spyair song lyrics has many variations in reletationship of proximity of time and space, and form of metonymy.Key Words: Meaning, Metonymy, Japanese Song Lyrics, Time And Space Proximity